The occurrence of postoperative atrial fibrillation according to different surgical settings in cardiac surgery patients - Jakubová, Marta (Oxford University Press, 2012)
OBJECTIVES: Atrial fibrillation is the most common arrhythmia after cardiac surgery. The pathogenesis of postoperative atrial fibrillation is multifactorial. The aim of the study was to analyse preoperative, intraoperative and postoperative factors and their relationships with the occurrence and duration of atrial fibrillation. METHODS: One hundred and ninety-six patients with coronary heart disease (152 men, age 62.7 ± 10.1 years) underwent surgical revascularization. Extracorporeal circulation was used in 64 patients and minimal extracorporeal circulation was used in 75 patients. Fifty-seven patients underwent surgery without extracorporeal circulation. During the first three postoperative days, subjects were monitored for the duration and incidence of atrial fibrillation, laboratory markers of inflammation (C-reactive protein, leucocytes) and serum potassium. RESULTS: Demographic data and associated cardiovascular diseases in the groups were not statistically different. The overall incidence of atrial fibrillation was 56% (110 patients). The highest incidence of atrial fibrillation was found in the extracorporeal circulation subgroup, with a significantly lower incidence using minimal extracorporeal circulation, and in patients operated on without extracorporeal circulation (75 vs 47 vs 46%, P <0.001). The longest duration of atrial fibrillation was found in patients operated on with extracorporeal circulation compared with minimal extracorporeal circulation, and without extracorporeal circulation (9.7 ± 11.6 vs 4.9 ± 8.3 vs 3.1 ± 5.2, P ≤0.001). The incidence of postoperative atrial fibrillation significantly correlated with elevation of inflammatory markers (C-reactive protein, leucocytes) compared with patients who were free of atrial fibrillation (P ≤0.001, P ≤0.05). The values of serum potassium were not significantly different. The relationship between postoperative atrial fibrillation and echocardiographic parameters was not confirmed. CONCLUSIONS: The use of extracorporeal circulation leads to a higher incidence of postoperative atrial fibrillation compared with the use of minimal extracorporeal circulation or with surgery without extracorporeal circulation, probably due to enhanced systemic inflammatory response.